2017
DOI: 10.1002/mrm.26798
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Gaussian diffusion imaging with a fractional order calculus model to predict response of gastrointestinal stromal tumor to second‐line sunitinib therapy

Abstract: The non-Gaussian FROC diffusion model showed clinical value in early prediction of gastrointestinal stromal tumor response to second-line sunitinib targeted therapy. The pretreatment FROC parameter β can increase the predictive accuracy when combined with the change in diffusion coefficient during treatment. Magn Reson Med 79:1399-1406, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…Using an FROC model with a combination of the pretreatment β value and posttreatment change of ADC at 2 weeks, Tang et al demonstrated that GIST response to sunitinib second-line targeted therapy can be assessed at early as 2 weeks after the initiation of therapy. 14 Figure 9 shows an example illustrating the sensitivity of β from the FROC model to sunitinib targeted therapy. Parameters from Gaussian and non-Gaussian diffusion models can also be combined across a broad b-value range to improve the performance of response to chemotherapy, as recently demonstrated by Zhu et al, for locally advanced rectal cancer.…”
Section: Dwi For Assessment Of Early Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Using an FROC model with a combination of the pretreatment β value and posttreatment change of ADC at 2 weeks, Tang et al demonstrated that GIST response to sunitinib second-line targeted therapy can be assessed at early as 2 weeks after the initiation of therapy. 14 Figure 9 shows an example illustrating the sensitivity of β from the FROC model to sunitinib targeted therapy. Parameters from Gaussian and non-Gaussian diffusion models can also be combined across a broad b-value range to improve the performance of response to chemotherapy, as recently demonstrated by Zhu et al, for locally advanced rectal cancer.…”
Section: Dwi For Assessment Of Early Responsementioning
confidence: 99%
“…5 Although the majority of tissue microstructural studies are performed on the brain, applications to the non-central nervous system (CNS) have emerged, including but not limited to prostate cancer, 12 breast cancer, 13 and gastrointestinal stromal tumor (GIST). 14 In this review we focus on the three aforementioned aspects-cellularity, vascularity, and microstructuresthat diffusion MRI can offer for cancer detection, characterization, and therapy evaluation. A special emphasis will be placed on microstructural characterization at high b-values, given its novelty and lack of systematic review in this rapidly growing area with immense potential.…”
mentioning
confidence: 99%
“…First, the lowest b value possible is only 0 s/mm 2 on our machine, and the ADC value may be influenced by microscopic perfusion. The use of low b values of 200–400 s/mm 2 with the IVIM model and FROC model [ 16 18 ] would be more sensitive to diffusion. Second, we could not use the contrast-enhanced sequence repeatedly over a short time period because of ethical reasons, which may have introduced bias in the judgement of cystic or myxoid degeneration only by T1WI and T2WI.…”
Section: Discussionmentioning
confidence: 99%
“…Among numerous anomalous diffusion models, the continuous‐time random‐walk (CTRW) model and the fractional motion (FM) model are actively pursued by the biophysics community and regarded as the major “archrivals” . The CTRW model, which recognizes intra‐voxel diffusion heterogeneity in both time and space, has already been introduced to the diffusion MRI community and successfully demonstrated in a number of clinical applications . The FM model, on the other hand, describes the complex diffusion process based on the intricate statistical properties, such as variances and correlations .…”
Section: Introductionmentioning
confidence: 99%
“…17 The CTRW model, which recognizes intra-voxel diffusion heterogeneity in both time and space, has already been introduced to the diffusion MRI community and successfully demonstrated in a number of clinical applications. [3][4][5][6][7][8][18][19][20] The FM model, on the other hand, describes the complex diffusion process based on the intricate statistical properties, such as variances and correlations. 15,17 Based on the Langevin equation, 21 one of the fundamental differential equations to describe stochastic dynamics of motion in a randomly fluctuating environment, 22,23 the FM model provides an alternative avenue to probing the complexity and the stochastic characteristics of diffusion in biological tissues.…”
mentioning
confidence: 99%